Exploring How Animal-Protein Sources (Eggs, Meat and Milk) Relate to Students’ Active Participation in Physical Education at The Indonesian School in Makkah - Muhammad Askari Zakariah; M. Arif Subair; Novita; Failal Ulfi Mauliah; Ambo Dalle; Aiedil Pebri Suwarna (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This qualitative-descriptive pilot study explored how animal-protein sources (eggs, meat, and milk/dairy) relate to students’ active participation in Physical Education (PE) at the Indonesian School in Makkah. Data were collected using an anonymous structured questionnaire with a two-week recall period covering respondent characteristics, frequency of animal-protein intake, perceived energy/recovery/comfort during PE, and perceived active participation in PE; responses were interpreted thematically to identify recurring patterns without causal inference. Ten students completed the questionnaire (all male adolescents, approximately 12–19 years), and most reported extracurricular sport participation. Four themes emerged: students framed active participation as disciplined engagement across lesson phases, persistence during drills and games, and social engagement through teamwork and sportspersonship; eggs, meat, and milk/dairy were typically reported as routine dietary habits rather than deliberate “PE-day strategies”; perceived readiness for PE was expressed mainly through energy versus fatigue and bodily comfort, suggesting diet may relate to participation indirectly through situational physical readiness; and participation barriers appeared multifactorial, implying strong contributions from non-nutritional influences such as lesson demands and the social–pedagogical climate. Overall, animal-protein sources were not described as direct determinants of PE participation in this small sample, highlighting the need for larger, more diverse studies that add open-ended interviews and consider key covariates (e.g., breakfast habits, hydration, sleep, and PE motivation) to clarify how nutrition and learning environments jointly shape active participation.